KLF11 (Krüppel-Like Factor 11) Inhibits Arterial Thrombosis via Suppression of Tissue Factor in the Vascular Wall. Issue 3 (March 2019) - Liang, Wenying; Fan, Yanbo; Lu, Haocheng; Chang, Ziyi; Hu, Wenting; Sun, Jinjian; Wang, Huilun; Zhu, Tianqing; Wang, Jintao; Adili, Reheman; Garcia-Barrio, Minerva T.; Holinstat, Michael; et al.
Abstract : Objective—: Mutations in Krüppel like factor-11 ( KLF11 ), a gene also known as maturity-onset diabetes mellitus of the young type 7, contribute to the development of diabetes mellitus. KLF11 has anti-inflammatory effects in endothelial cells and beneficial effects on stroke. However, the function of KLF11 in the cardiovascular system is not fully unraveled. In this study, we investigated the role of KLF11 in vascular smooth muscle cell biology and arterial thrombosis. Approach and Results—: Using a ferric chloride–induced thrombosis model, we found that the occlusion time was significantly reduced in conventional Klf11 knockout mice, whereas bone marrow transplantation could not rescue this phenotype, suggesting that vascular KLF11 is critical for inhibition of arterial thrombosis. We further demonstrated that vascular smooth muscle cell–specific Klf11 knockout mice also exhibited significantly reduced occlusion time. The expression of tissue factor (encoded by the F3 gene), a main initiator of the coagulation cascade, was increased in the artery of Klf11 knockout mice, as determined by real-time quantitative polymerase chain reaction and immunofluorescence. Furthermore, vascular smooth muscle cells isolated from Klf11 knockout mouse aortas showed increased tissue factor expression, which was rescued by KLF11 overexpression. In human aortic smooth muscle cells, small interfering RNA–mediated knockdown of KLF11 increased tissue factor expression. Consistent results were observed on adenovirus-mediated overexpression of KLF11. Mechanistically, KLF11 downregulates F3 at the transcriptional level as determined by reporter and chromatin immunoprecipitation assays. Conclusions—: Our data demonstrate that KLF11 is a novel transcriptional suppressor of F3 in vascular smooth muscle cells, constituting a potential molecular target for inhibition of arterial thrombosis. Abstract : Supplemental Digital Content is available in the text.